Synthesis of 2-amino-5-methylpyridinium tetrachloridocadmate(II) (C6H9N2)2[CdCl4]: Structure, DFT-calculated descriptors and molecular docking study - Ikram Jomaa; Fehmi Bardak; Noureddine ISSAOUI; Aurelio Cabeza; Duane Choquesillo-Lazarte; Ahmet Atac; Houda Marouani; Omar M. Al-Dossary (Journal of King Saud University: Science, 2024)
In this research paper, (C6H9N2)2[CdCl4], was effectively synthesized using the slow solvent evaporation procedure. Single crystal X-ray diffraction (scXRD) analysis revealed that the compound crystallizes in the triclinic system, specifically in the space group P 1¯. Powder XRD (PXRD) of the bulk material showed some minor impurities. The atomic arrangement of the title structure comprises discrete tetrahedral groups [CdCl4]2− linked to the organic entities through weak N(C)H…Cl hydrogen bonds. Solid-state contacts were further studied through Hirshfeld surface analyses, complemented by 2D fingerprint plots. Computational results, obtained using the B3LYP tool with 6-311++G(d,p) + LANL2DZ mixed basis set, demonstrated consistent geometrical, vibrational, and electronic features to the experimental data. Non-covalent interactions were explored in depth using Atoms-In-Molecule (AIM) and Reduced Density Gradient (RDG) analyses. Thermogravimetry (TG) and Differential Scanning Calorimetry (DSC) analyses showed melting at 378 K and decomposition at around 540 K. Furthermore, the inhibition activity of the examined compound was explored in-silico through molecular docking studies targeting the inducible Nitric Oxide Synthase (iNOS) enzymes.